The fungal genus Calycellinopsis belongs in Helotiaceae not Dermateaceae - Zhuang, Wen-Ying; Luo, Jing; Zhao, Peng (Phytotaxa, 2013)
The monotypic genus Calycellinopsis was known previously only from the type locality in tropical Yunnan, China and treated as a member of the Dermateaceae based on morphological features. When the second collection from Hunan in the subtropical region was found, a sequence analysis of 18S nrDNA showed that the fungus is closely related to fungi in the Helotiaceae and only distantly related to members of the Dermateaceae. A transfer of Calycellinopsis from Dermateaceae to Helotiaceae is required.